2018
DOI: 10.1080/00905992.2017.1381676
|View full text |Cite
|
Sign up to set email alerts
|

Pride and shame in collective memory of Russian and American youths

Abstract: This article examines collective attitudes of American and Russian students toward national historical events that elicit pride or shame. The authors use the results of a quantitative questionnaire and analysis of in-depth interviews among students of leading American and Russian universities to identify the temporal localization, the content structure, and the prevalence of either hard or soft power in students' attitudes of pride or shame. The authors argue that perceptions of the past have been a core compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…By replicating this so-called Judging the Past framework, McDonnell and Fine (2011) investigates pride and shame in national imagining among the youth in Ghana. Most recently, Kasamara et al (2018) used this model to study national events of pride and shame to be observed in memory perceptions among Russian and American youths. As McDonnell and Fine (2011) assert, what Schwartz and others provide is “the central body of work examining the emotive content of culture of memory, particularly focusing on the dual nature of national pride and shame” (p. 141; footnote #2).…”
Section: Methodsmentioning
confidence: 99%
“…By replicating this so-called Judging the Past framework, McDonnell and Fine (2011) investigates pride and shame in national imagining among the youth in Ghana. Most recently, Kasamara et al (2018) used this model to study national events of pride and shame to be observed in memory perceptions among Russian and American youths. As McDonnell and Fine (2011) assert, what Schwartz and others provide is “the central body of work examining the emotive content of culture of memory, particularly focusing on the dual nature of national pride and shame” (p. 141; footnote #2).…”
Section: Methodsmentioning
confidence: 99%
“…The discourse of a nation with strong continuity destabilized periodically by the conspiracies of the West is replicated in vernacular narratives in connection to deteriorated diplomatic relations with the USA and Europe in recent years (Blackburn 2018). Official hailing of Soviet achievements is well received, with nationwide polls recording increasing nostalgia for the USSR (Levada Center 2019) and Soviet memory seen as a point of connection with the national past among young people (Kasamara, Sorokina, and Maximenkova 2018). The annexation of Crimea in 2014 boosted patriotic sentiment, superseding ethnic minority resentment of assimilatory policies as well as middle-class disaffection with Putin's erosion of democracy that surfaced around his third election to presidential office (Sharafutdinova 2020).…”
Section: Challenges To Russian Nation Building and The Role Of Local ...mentioning
confidence: 99%
“…Researchers have conducted both case studies of particular countries (McDonnell and Fine 2011), and have also drawn on comparative perspectives. These studies make it possible to track differences between countries, in terms of which events become sources of pride and/or shame, how these events are interpreted, and how they are experienced (Kasamara, Sorokina, and Maximenkova 2018; Schwartz, Fukuoka and Takita-Ishii 2005; Schwartz and Kim 2001; Zhang and Schwartz 1997).…”
Section: Empirical Collective Memory Studiesmentioning
confidence: 99%
“…Within the framework of this project, polls are being conducted in Russia, the United States, the United Kingdom, Germany, France, China, South Korea, Japan, and Venezuela. Several studies have already been published based on the analysis of the collected data (Kasamara, Sorokina, Maximenkova 2018; Sorokina and Maximenkova 2020; Katrich 2021). The data collected during the realization of the project are used in this study, as well.…”
mentioning
confidence: 99%